Peningkatan Keaktifan dan Hasil Belajar IPS melalui Model Pembelajaran Kooperatif Tipe Teams Game Tournament (Tgt) pada Siswa Kelas IV SD N Sumberwungu 1 Kepanewon Tepus Kabupaten Gunungkidul - Nur Achmad Guntur Saputra; Gunawan Sridiyatmiko (Proceedings Series on Social Sciences & Humanities, 2022)
The selection of learning models used by teachers in learning activities it one of the determining factors for the success of student learning. This study aims to improve student activity and learning result through a cooperative learning model of the type of team game tournament (TGT) for fourth graders at SDN Sumberwungu I in the 2020/2022 academic year. This research is a classroom action research. This research was conducted at SDN Sumberwungu I. The subjects in this study were class IV students, totaling 10 students. Data collection techniques in this study used observation sheets and learning outcomes tests. The data analysis technique used quantitative and qualitative descriptive with percentages. The results showed that 1) The application of the cooperative learning model of the type of tournament team game (TGT) can increase student learning activities in fourth grade students of SD Sumberwungu I, it is proven that in the pre-cycles students have an interest in learning with a good category of at least 30% increasing in cycles I. 80% and in the second cycles 90%. 2) The application of the cooperative learning model of the type of team game tournament (TGT) can improve student learning outcomes, especially grade IV students at SDN Sumberwungu I, this can be seen in student learning completeness, in the pre-cycles students who excel the KKM 4 score 40% increase in the first cycles 8 80% students and in the second cycles increased to 9 students 90%. The increase was because the teacher put more emphasis on tournament rules, and the division of tasks in groups.